MOSQUE ARCHITECTURE AS A SUSTAINABLE BUILDING IN URBAN (Case Study: Al Markas Al Islamic Mosque Makassar) - Imriyanti, Imriyanti (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2013)
AbstractMosque Architecture is a part of Islamic architecture. Mosque should be fused with elements of nature because its function as a place to pray to God who created the universe. Al Markas Al Islamic Makassar mosque is used as a center of Islamic aspirations of the people and the government to accommodate all the activities of moslems in Makassar. Through this function, the provision of Al Markas Al Islamic mosque began from the desire of Islamic societies in Makassar, which wants the Islamic center to be equipped with facilities and infrastructure as well as architectural, monumental buildings and structures that can be last for hundreds of years (continuous), blend with the environment, and also can be used by the public. Having regard to the function of a mosque especially at the Al Markas Al Islamic Makassar mosque, then the problem that arise is how the Al Markas Al Islamic mosque can be survived/sustainable in order to function as a place of worship and as a center of Islam. This research is a descriptive qualitative research that is trying to generate data in the form of systematic and accurate picture of the object of study. The sustaiprophetlity of Al Markas AL Islamic mosque can be known through the concept of Islam in accordance with the view of Islam as well as the sustaiprophetlity of the buildings that seen in the spatial pattern of the mosque, appearance, natural lighting, natural ventilation, and user behavior of the mosque.Keywords: mosque architecture, sustaiprophetlity, view of Islam AbstrakArsitektur masjid merupakan bagian dari arsitektur Islam. Bangunan masjid sebaiknya dapat menyatu dengan unsur alam karena masjid difungsikan sebagai wadah dalam bersujud/sembahyang kepada Allah SWT yang menciptakan alam semesta ini. Masjid Al Markas Al Islamic Makassar merupakan kompleks kegiatan Islam yang digunakan sebagai pusat aspirasi masyarakat dan pemerintahan yang dapat menampung seluruh kegiatan umat Islam di Makassar. Melalui fungsi inilah maka pengadaan masjid Al Markas Al-Islamic bermula dari keinginan masyarakat Islam di kota Makassar, yang mana menginginkan pusat kegiatan Islam yang dilengkapi dengan sarana dan prasarana juga bangunannya monumental yang secara arsitektur dan struktur bisa bertahan sampai ratusan tahun (berkelanjutan), dan menyatu dengan lingkungannya serta dapat digunakan oleh masyarakat luas. Dengan memperhatikan fungsi masjid terutama pada masjid Al Markas Al Islamic Makassar maka permasalahan yang muncul adalah bagaimanakah arsitektur masjid Al Markas Al Islamic dapat bertahan/berkelanjutan agar dapat difungsikan sebagai tempat beribadah dan sebagai pusat kegiatan Islam. Penelitian ini merupakan penelitian deskriptif yang bersifar kualitatif yaitu penelitian yang berusaha menghasilkan data berupa gambaran yang sistematis dan akurat dari objek kajian. Keberlanjutan masjid Al Markas Al Islamic dapat diketahui melalui penyatuan konsep masjid Al Markas Al Islamic sesuai dengan pandangan Islam serta keberlanjutan dilihat pada bangunan yakni pola tata ruang masjid, penampilan, pencahayaan dan penghawaan alami serta perilaku pemakai masjid.Kata Kunci : Arsitektur masjid, keberlanjutan, pandangan Islam